Estudio isotérmico de remoción de cromo (VI) en solución acuosa empleando perlas de alginato con Chlorella sp. inmovilizada. - Urvina Ulloa, Jeaneth Andrea (2018)
The objective of the present investigation was to study the removal of chromium (VI) in aqueous solution by means of isothermal models using alginate beads with Chlorella sp. immobilized and alginate beads without Chlorella sp.; the removal was evaluated using solutions of chromium at different concentrations. To determine the kinetics of removal, samples of aqueous solution were obtained in a range of 0-240 minutes. Then, the removal of the metal at pH 4 and 5 and at different cell densities of Chlorella sp. (0.3x107; 1.6x107; 3x107 cells/mL of alginate). Finally, the effect of the initial concentration of chromium was evaluated, analyzing six concentrations (0-20 mg/L). All the tests were analyzed by Atomic Absorption spectrometer, obtaining the highest percentage of removal at a contact time of 224 min, pH 5 and 3x107 cells/mL with 81.09% and 72.20% removal by the action of the alginate beads with Chlorella sp. and alginate beads without Chlorella sp, respectively. Three isothermal models were analyzed, the Langmuir isotherm being the one that was best adjusted to describe the adsorption process, determining a maximum adsorption capacity of 5.08 mg/g for alginate beads with Chlorella sp. and 3.74 mg/g for the alginate beads without Chlorella sp, concluding that there is a greater adsorption capacity when immobilizing Chlorella sp. in pearls of alginate. In addition, the isothermal analysis allows to recommend its possible use in the treatment of water contaminated with chromium (VI).